Extracorporeal life support to ventricular assist device: potential benefits of sternal-sparing approach - Sagebin, Fabio M. (J Thorac Dis, 2019)
BACKGROUND: Advancements in left ventricular assist device (LVAD) technology have improved long-term survival for properly selected patients with advanced heart failure. However, the subset of patients in critical cardiogenic shock remain difficult to treat with persistently high patient morbidity and mortality. The goal of this study is to describe our institutional experience utilizing extracorporeal membrane oxygenation (ECMO) as a bridge to LVAD for patients in cardiogenic shock comparing the less invasive complete sternal-sparing (CSS) surgical technique to median sternotomy. METHODS: Data was collected as a single center retrospective review of patients implanted with a continuous-flow LVAD directly off ECMO from 2012 to 2018. Patients were stratified by LVAD surgical technique. The primary outcome was survival to discharge. Secondary outcomes included postoperative complications, resource utilization and survival at 6-months. RESULTS: Of the 37 patients implanted directly off ECMO, 26 (70%) patients were implanted via median sternotomy and 11 (30%) patients by the CSS approach. Median time on ECMO support was 8 days (range, 2–29 days). Preoperative characteristics were similar between groups. Survival to discharge was 78% overall (73% vs. 91% CSS, P=0.391). The CSS cohort had fewer postoperative complications, including fewer transfusions (P=0.044) and trend towards less right ventricular (RV) failure (62% vs. 27% CSS, P=0.079). Both cohorts required similar median length of stay (LOS) in the intensive care unit (ICU) (11 vs. 12 days, P=0.695) and similar overall hospital LOS (34 vs. 22 days, P=0.242). Overall survival was 74% at six months (68% vs. 89% CSS, P=0.386). CONCLUSIONS: VA ECMO can be used effectively as a bridge-to-LVAD for patients in cardiogenic shock. The less invasive CSS approach demonstrates potential advantages to median sternotomy. Further study is needed to better understand the benefits of less invasive surgical techniques.